Isolation of Bifidobacteria infantis and its antagonistic activity against ETEC 0157 and Salmonella typhimurium S-285 in weaning foods - Mohd Yusof, Rokiah; Haque, Formuzul; Ismail, Maznah; Hassan, Zaiton (Wiley, 2000)
Probiotic organism Bifidobacteria was isolated from the faeces of breast-fed infants at Universiti Putra Malaysia. Trypticase phytone peptone yeast extract agar (TPY) was used as a selective media for the isolation. Morphological examination of the isolates indicated that Bifidobacteria was Gram-positive rods in nature, curved with characteristics of V and Y shapes. The organisms were non-catalase producing, non-nitrate reducing, non-motile, had an absence of indole and were unable to liquify gelatin. The ratios of acetic and lactic acids were determined using high performance liquid chromatography (HPLC). Using carbohydrate fermentation profile test API-CH-50 kits, 20 Bifidobacteria strains had been identified: they were the species of Bifidobacteria infantis and two different sub-species, mainly infantis and lacentis. Based on a wide zone of inhibition, three suitable strains of B. infantis, Bifi-11, Bifi-19 and Bifi-20, were tested in weaning foods for antimicrobial activity towards two human pathogens: E. coli-0157 (World Health Organization) and Salmonella typhimurium S-285. The pH, titratable acidity of weaning foods and total colony count for Bifidobacteria, enteropathogenic Escherichia coli and S. typhimurium were recorded at 3-h intervals for 30 h. It was found that after 9 h of incubation of weaning foods, the pH declined to < 3.6 from pH 6.0, whereas titratable acidity increased from 0.026 to 0.08%. It was indicated that Bifidobacteria inhibited E. coli better than did S typhimurium due to low pH. After 24 h of incubation, approximately 98% of E. coli was inhibited by Bifidobacteria. It is suggested that the inhibitory effect of Bifidobacteria strains in weaning foods towards the growth of enteropathogenic E. coli and S. typhimurium was solely due to low pH and the production of volatile acid components by the organism.